PERILAKU PENYIMPANGAN SEKSUAL: STUDI KEKERASAN SEKSUAL MASA LALU DALAM PEMBENTUKAN PERILAKU PEDOFILIA NARAPIDANA LAPAS KLATEN - Nurwulan sinta, Sinta Nurwulan; Alfin Miftahul Khairi (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2023)
This study aims to reveal that past trauma experienced by a person can shape pedophilic behavior in the future. The trauma experienced during the schoolchildren phase is the strongest memory phase covering the events experienced. This study uses a qualitative method with a case study approach. The population in this study were convicts of sexual harassment cases in general at the Class IIB Klaten correctional facility. While the research subjects were selected by the researcher using a purposive sampling technique with the following criteria, namely inmates with cases of underage sexual harassment and there were 5 inmates with these criteria but with different causal factors. Data collection techniques using observation, interviews and documentation. The results of the study of the three subjects who had the same factors as perpetrators of pedophilia were caused by past trauma in childhood getting acts of sexual harassment by acts of sodomy by those closest to them without rebelling. From the events experienced by the three subjects, they made the decision not to tell their bad experiences to their parents or the people around them, so this decision added to the feeling of trauma which affected their sexual condition to deviate. victims of sexual violence become perpetrators of pedophilia in the future. Keywords: sexual deviance,sexual violence, pedophilia